The SYNERGY biodegradable polymer everolimus eluting coronary stent: Porcine vascular compatibility and polymer safety study. Issue 6 (23rd May 2015) - Wilson, Gregory J.; Marks, Angela; Berg, Kimberly J.; Eppihimer, Michael; Sushkova, Natalia; Hawley, Steve P.; Robertson, Kimberly A.; Knapp, David; Pennington, Douglas E.; Chen, Yen‐Lane; Foss, Aaron; Huibregtse, Barbara; et al.
Abstract : Aims: SYNERGY is a novel platinum chromium alloy stent that delivers abluminal everolimus from an ultrathin poly‐lactide‐ co ‐glycide (PLGA) biodegradable polymer. This study evaluated the in vivo degradation of the polymer coating, everolimus release time course, and vascular compatibility of the SYNERGY stent. Methods and Results: SYNERGY stents were implanted in arteries of domestic swine. Devices were explanted at predetermined time points (up to 120 days) and the extent of PLGA coating or everolimus remaining on the stents was quantified. Everolimus levels in the arterial tissue were also evaluated. A pathological analysis on coronary arteries of single and overlapping stents was performed at time points between 5 and 270 days. PLGA bioabsorption began immediately after implantation, and drug release was essentially complete by 90 days; PLGA absorption was substantially complete by 120 days (>90% of polymer was absorbed) leaving a bare metal SYNERGY stent. Vascular response was similar among SYNERGY and control stents (bare metal, polymer‐only, and 3× polymer‐only). Mild increases in para‐strut fibrin were seen for SYNERGY at an early time point with no significant differences in all other morphological and morphometric parameters through 270 days or endothelial function (eNOS immunostaining) at 90 or 180 days. Inflammation was predominantly minimal to mild for all device types. Conclusion: In a swine model, everolimus was released by 90 days and PLGA bioabsorption was complete shortly thereafter. The SYNERGY stent and its biodegradable polymer, even at a 3× safety margin, demonstrated vascular compatibility similar to bare metal stent controls. © 2015 Wiley Periodicals, Inc.